1993
DOI: 10.1152/ajpendo.1993.264.2.e197
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in polycystic ovary syndrome: decreased expression of GLUT-4 glucose transporters in adipocytes

Abstract: We have found that women with polycystic ovary syndrome (PCOS) have decreased sensitivity and responsiveness to insulin. The present study was performed to determine whether this impaired insulin responsiveness was associated with diminished GLUT-4 glucose transporter content in adipocytes. Insulin-stimulated glucose transport and GLUT-4 abundance were measured in abdominal adipocytes from obese (n = 9) and lean (n = 7) PCOS as well as obese (n = 8) and lean (n = 8) control women matched for age and weight. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
120
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 25 publications
7
120
0
2
Order By: Relevance
“…27 Rosenbaum et al also demonstrated that the insulin resistance on the glucose transport is strictly associated with a decreased expression of GLUT-4 glucose transporters in adipocytes. 28 …”
Section: Testosteronementioning
confidence: 99%
“…27 Rosenbaum et al also demonstrated that the insulin resistance on the glucose transport is strictly associated with a decreased expression of GLUT-4 glucose transporters in adipocytes. 28 …”
Section: Testosteronementioning
confidence: 99%
“…First, resistance to the action of insulin affects peripheral glucose uptake and insulin-mediated suppression of lipolysis, but does not appear to extend to the hepatic actions of insulin (Peiris et al, 1989;Dunaif, 1993). This is borne out by the well recognized, inverse relationship of serum concentrations of insulin and sex hormone binding globulin (SHBG), which is presumed to be a reflection of the direct inhibitory action of insulin on SHBG synthesis by the liver (Plymate et al, 1988;Conway et al, 1990;Sharp et al, 1991;Hamilton-Fairley et al, 1995).…”
Section: Insulin Resistance In Polycystic Ovary Syndromementioning
confidence: 99%
“…The differences in insulin sensitivity between PCOS and BMI-matched control groups are no longer significant if the distribution of body fat is taken into account (Robinson et al, 1992;Holte et al, 1994). Third -and this is not surprising, given the apparently tissue-selective nature of insulin resistance -there is little evidence for a primary abnormality in the insulin receptor in PCOS (Dunaif, 1993). While it is true that genetically determined defects in the insulin receptor can lead to the development of a PCOS-like syndrome, it must be conceded that women with these receptor disorders constitute only a very small proportion of those presenting with hyperandrogenism (Dunaif, 1993).…”
Section: Insulin Resistance In Polycystic Ovary Syndromementioning
confidence: 99%
See 2 more Smart Citations